Relationship between Working Capital Management, Corporate Social Responsibility, Liquidity Risk, and Profitability on the Performance and Sustainability - Heliani, Heliani (International Journal of Business, Law, and Education, 2023)
The objective of this study is to investigate the correlation among working capital management, corporate social responsibility, liquidity risk, profitability, performance, and sustainability in Indonesian manufacturing companies. Data were collected from 150 companies in West Java, Indonesia, and analyzed using the PLS-SEM approach. The analysis results show working capital management, corporate social responsibility, and liquidity risk have a significant positive effect on profitability, which in turn has a positive impact on performance and sustainability. These results support the research and provide insights into the importance of managing working capital, adopting corporate social responsibility practices, and reducing liquidity risk to improve profitability, performance, and sustainability in Indonesian manufacturing companies.